Digitalization and Creative Health to Empower Posyandu Cadres in Yogyakarta City's Effort to Zero Case Stunting - Nurhadi Wijaya Sugiarto; Windi Vensia Putri; Anggie Puspita Dewi; Nurkhasanah; Herliana Riska (Community Development Journal, 2023)
The stunting problem in Umbulharjo, Yogyakarta City, ranks second among 18 other regions, with 118 children under five. Because posyandu plays a crucial role in speeding the elimination of stunting, the capacity of cadres must be considered. According to the findings of the multi-factorial FGD, the causes of stunting in Umbulharjo Village are a lack of optimum counseling and eating patterns for market-dependent children. The goal is to enhance health independence and food security by creating an anti-stunting sustainable food yard (P2L) and a digital-based information system, with a target of 23 posyandu cadres. Asset Based Community Development (ABCD) employs a method that covers requirements analysis, design, mentorship, and implementation and evaluation stages. Results: The cadres' knowledge of vegetable gardening went from 16% to 75%, their skills increased from 7% to 70%, and their motivation to plant vegetables increased from 55% to 90%. Similarly, cadres' average understanding of the processing of diverse local food ingredients improved from 30% to 75%, and their educational ability increased from 5% to 70%. Conclusion: Empowering posyandu cadres to achieve zero stunting in Yogyakarta through digital and creative health has expanded natural and human resource capacity in Umbulharjo Village, Yogyakarta City